Mandibular Reconstruction With the Contralateral Vascularized Iliac Flap Using Individual Design: Iliac Crest Used to Reconstruct the Ramus and the Anterior Border of the Iliac Wing Used to Reconstruct the Inferior Border: A Case Report - Xu, Guangcai; Jia, Ju; Xiong, Xuepeng; Peng, Liwei; Bu, Lin-lin; Wang, Xiqian (Frontiers in Surgery, 2022)
Mandible defects resulting from resection of benign or malignant lesions, trauma, or radionecrosis are commonly encountered in the oral and maxillofacial department. Vascularized bone flaps, in general, provide the best functional and aesthetic outcome. The iliac crest provides a large piece of curved cortico-cancellous bone, measuring 6–16 cm in length. It has a natural curvature that complements the curve of the lateral and sometimes anterior mandible and can be placed accordingly to fill defects. In the paper, we report a mandibular reconstruction with a vascularized iliac flap using individual virtual preoperative planning and 3D printing technology. We want to offer a new design idea for mandibular defect reconstruction.